Orthotic control of rear foot and lower limb motion during running in participants with chronic Achilles tendon injury - Donoghue, O. A.; Harrison, A. J.; Laxton, P.; Jones, R. K. (Sports Biomechanics, 2008)
This study examined the kinematic effects of orthoses in participants with a history of chronic Achilles tendon injury. Twelve participants ran at self-selected speeds on a treadmill with and without customized orthoses. Joint and segment angles including leg abduction, calcaneal, eversion, ankle dorsiflexion, and knee flexion angles were calculated from three-dimensional data throughout stance. Five footfalls were obtained for each participant and condition. Statistical tests revealed an increase in maximum eversion with orthoses. In the individual participant analysis, this was evident in 9 of 12 participants. Trends towards increased eversion range of motion and decreased ankle dorsiflexion maximum and range of motion angles were also observed. Increased eversion was unexpected as all devices were designed to provide pronation control as deemed necessary by the podiatrist. Despite this, participants reported between 50 and 100% (average 92%) relief from symptoms with the use of orthoses. Further analysis of the angle-time curves and coordination between angular measures is recommended.